2020
DOI: 10.1037/pspa0000191
|View full text |Cite
|
Sign up to set email alerts
|

Does spending money on others promote happiness?: A registered replication report.

Abstract: Harvard Business SchoolResearch indicates that spending money on others-prosocial spending-leads to greater happiness than spending money on oneself (e.g., Dunn, Aknin, & Norton, 2008. These findings have received widespread attention because they offer insight into why people engage in costly prosocial behavior, and what constitutes happier spending more broadly. However, most studies on prosocial spending (like most research on the emotional benefits of generosity) utilized small sample sizes (n Ͻ 100/cell).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 36 publications
12
81
0
1
Order By: Relevance
“…People who help others are happier. Research from diverse samples and in various countries has shown both correlational and causal links between prosocial actions and subjective well-being outcomes (e.g., Aknin et al, 2013Aknin et al, , 2015Aknin et al, , 2020Borgonovi, 2008;Dunn et al, 2008;Haski-Leventhal, 2009;Lyubomirsky et al, 2005;Nelson et al, 2016). For instance, students randomly assigned to commit five kind acts in a single day each week for 6 weeks were significantly happier than a control group (Lyubomirsky et al, 2005).…”
Section: Special Characteristics Of Prosocial Behaviormentioning
confidence: 99%
“…People who help others are happier. Research from diverse samples and in various countries has shown both correlational and causal links between prosocial actions and subjective well-being outcomes (e.g., Aknin et al, 2013Aknin et al, , 2015Aknin et al, , 2020Borgonovi, 2008;Dunn et al, 2008;Haski-Leventhal, 2009;Lyubomirsky et al, 2005;Nelson et al, 2016). For instance, students randomly assigned to commit five kind acts in a single day each week for 6 weeks were significantly happier than a control group (Lyubomirsky et al, 2005).…”
Section: Special Characteristics Of Prosocial Behaviormentioning
confidence: 99%
“…When participants rated their current emotion right after their purchase, participants in the prosocial spending condition (those that spent money on others) reported feeling significantly happier than those who spent money on themselves (Aknin et al., 2020; see also Whillans et al., 2019). The happiness benefits observed in this study were roughly similar to other well‐established predictors of happiness, such as marital status (Helliwell & Putnam, 2004) and income (Stevenson & Wolfers, 2013).…”
Section: Helping and Happiness: An Overviewmentioning
confidence: 99%
“…The happiness benefits observed in this study were roughly similar to other well‐established predictors of happiness, such as marital status (Helliwell & Putnam, 2004) and income (Stevenson & Wolfers, 2013). Yet, the strength of this effect depends on the methods used (Aknin et al., 2020). People experienced greater emotional benefits from actually participating in an act of helping in the lab as opposed to simply thinking about doing so.…”
Section: Helping and Happiness: An Overviewmentioning
confidence: 99%
“…Proposed solutions to bridge this gap include (a) greater publication of incremental and, where appropriate, non-significant findings; (b) the use of increased power and greater sample sizes; (c) preregistration; (d) single-paper meta-analyses; (e) reporting all, rather than only significant, studies conducted; and, (f) data transparency-among many other recommendations [15][16][17][18][19][20]. Following such recommendations, studies retesting published findings and employing one or a combination of the proposed solutions are becoming commonplace [c.f., [21][22][23]. The present paper draws on such recommendations to reexamine the relation between optimism and counterfactual direction of comparison.…”
Section: Goal Of the Present Researchmentioning
confidence: 99%